Charles Boyer the French lover - Baxter, John, 1939- (University Press of Kentucky, 2021)
Charles Boyer: The French Lover is the first biography of Boyer to exist in English in almost forty years. Author John Baxter artfully presents the often-tragic life of this often overlooked, yet profoundly impactful French actor. Baxter relates how Boyer (1899-1978) established himself in the theater and cinema of France, confidently transitioning from silent film to sound and making a name for himself as a romantic leading man in Hollywood through the early 1940s. During World War II, Boyer put his career on hold to become politically active on behalf of his occupied home country. Upon returning to the stage and screen, Boyer adapted effortlessly to postwar character roles in both Europe and the United States. He entered television in the 1950s as both producer and performer, and then remade himself as a comedy performer in the 1960s. Nominated four times for Academy Awards, he was honored by the Academy only once-a special honorary award received for his activities on behalf of France during World War II.